The analysis of characterisation of body scrub Lo’I Me’e made of rice - Amrullah, Shafwan; Nadila, Nadila; Amin, Muhamad (UNIVERSITAS MUHAMMADIYAH MATARAM, 2022)
Several lulurus products have been spread as the main product in skin care. Besides that, traditional scrub products have become another alternative choice for Indonesian people because they are known to have good advantages. However, this traditional scrub lacks knowledge of its composition and characteristics. One of them is Bima's signature black scrub, Lo'I Me'e. So that in this study a physical and chemical testing process was carried out on the lo'I Me'e black scrub. The research began with making scrubs, which are made from coffee, rice, and also the addition of tamarind. The formula used is a formula that is generally used as a Lo'I Me'e scrub product. The results of the study were tested for characteristics in the form of skin irritation test, moisture content, pH value test and antioxidant test (IC50). The results obtained in this study included no skin irritation from the public test results. In addition, the average water content produced is 34.4%. The resulting anti-oxidant levels show an average number of 35.20 IC50. While the pH value test produced was 5. All of these results met the Indonesian National Standard (SNI) regarding physical and chemical tests of scrubs.